2019
DOI: 10.3390/su11071839
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–Temporal Analysis of Urban Land-Use Efficiency: An Analytical Framework in Terms of Economic Transition and Spatiality

Abstract: Rapid urban expansion may cause a decline in land-use efficiency and result in a series of social and ecological problems. Economic transition has significantly influenced urban land development, and provides a good perspective for analyzing changes in land-use efficiency. This paper primarily discusses the theoretical influence of economic transition on urban land-use efficiency. Using 126 cities in the Yangtze River Economic Zone as examples, we explore the spatial–temporal characteristics of changes in land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Thus, the Scientific Committee on Problems of the Environment proposed a new method that could overcome this shortcoming. Based on China's national conditions, Chinese scholars have constructed a comprehensive evaluation index for the RES that considers resource conservation, economic level and urban charm [45][46][47][48][49]. The RES should be evaluated quantitatively.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the Scientific Committee on Problems of the Environment proposed a new method that could overcome this shortcoming. Based on China's national conditions, Chinese scholars have constructed a comprehensive evaluation index for the RES that considers resource conservation, economic level and urban charm [45][46][47][48][49]. The RES should be evaluated quantitatively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The RES should be evaluated quantitatively. Methods include a comprehensive weighted-average index, an analytic hierarchy, and a fuzzy comprehensive evaluation [45][46][47][48][49]. As for how to develop the RES, scholars have mainly conducted research on the transformation of governmental functions, scientific and technological investments, and the transformation of economic development models [43][44][45].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional studies on land-use efficiency mostly targeted one of the aspects only, such as the development status, temporal and spatial distribution, regional disparity, or influence factors of land-use efficiency; a few consider two or three aspects. Among them, they were either limited to one province or one region and were not extended to the whole country, or the research period was relatively short and only studied the land-use efficiency for several years [19,[24][25][26][27]. In addition, among Sustainability 2019, 11,4756 3 of 22 studies on the influence factors of land-use efficiency, there is still a lack of researches that focuses on the perspective of demographic transition.…”
Section: An Analytical Frameworkmentioning
confidence: 99%
“…Xie et al [16] found that with the development of the economy, the efficiency of industrial land-use will decrease slightly. Meanwhile, some scholars have also studied the influencing factors of land-use from other perspectives, such as industrialization, globalization, tourism, and so on [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%